TANGGUNG JAWAB KPU TERHADAP PELAKSANAAN HAK PILIH WARGA NEGARA PADA PEMILIHAN ANGGOTA DEWAN PERWAKILAN RAKYAT DAERAH BERDASARKAN UU NO. 8 TAHUN 2012 TENTANG PEMILIHAN UMUM ANGGOTA DEWAN PERWAKILAN RAKYAT, DEWAN PERWAKILAN DAERAH, DAN DEWAN PERWAKILAN RAKY - ALOYSIUS DING, SH. A.21212007, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis studies raised the question "Responsibilities of the Commission of Implementation Suffrage Citizens On Election of Members of Provincial Parliament by Law No. 8 of 2012 on General Election of Members of the House of Representatives, Regional Representatives Council, and the Regional Representatives Council (Studies in the City Pontianak)". This study uses normative law research that is supported by empirical research/ sociological. The survey results revealed that the implementation of the right to vote of citizens in general elections members of the Regional Representatives Council (DPRD) in Pontianak not run as expected, because many people / citizens who have the right to vote are not registered in DPT or can not use their voting rights , The number of registered voters in the legislative election in Pontianak in 2014 both enrolled in the DPT, DPTb, deposits, and as many as 425 646 people DPKTb voters and exercise their voting rights as much as 314 313 voters or by 73.84%. If the number of voters who registered as many as 425 646 people compared to the number of potential voters Pontianak city population as much as 469 480 people, then there are 43 834 people who have the right to vote but are not registered or lose the right to vote in legislative elections in 2014 or by 9.34%. Efforts community / citizen who can not exercise their voting rights at the general election members of the Regional Representatives Council (DPRD) Pontianak City to report to the authorities and members of the Commission or anyone who caused it happened may be subject to criminal sanction as stipulated in Law OF No. 8 of 2012 for eliminating the constitutional ights of citizens to vote.Recommendations are: the Commission as an institution is given the authority to draw up the final voters list should work professionally and prepare DPT properly, so that no citizen who lost their constitutional rights in the legislative elections; and the Active Stetsel system in legislative elections, every citizen should actively look DPS / DPT, and if his name is not listed in the DPS / DPT, the concerned should submit an entry to be fixed, so that the concerned do not lose their constitutional rights.